Structure and Absolute Configuration of Auriculamide, a Natural Product from the Predatory Bacterium Herpetosiphon aurantiacus. Issue 14 (17th March 2015) - Schieferdecker, Sebastian; Domin, Nicole; Hoffmeier, Christine; Bryant, Donald A.; Roth, Martin; Nett, Markus
Abstract: The genome of the filamentous, predatory bacterium Herpetosiphon aurantiacus harbors a plethora of genes that are predicted to be involved in natural product biosynthesis. Until now, however, no secondary metabolites have been described from this microorganism. Analysis of H. aurantiacus culture extracts by 1 H NMR spectroscopy now led to the discovery of a chlorinated amide, which we termed auriculamide. The configuration of the three chiral centers in auriculamide was solved by chromatographic comparison with stereospecifically prepared reference compounds following chemical degradation. Furthermore, a putative gene cluster for the biosynthesis of auriculamide was identified by genome mining. Abstract : Chemical analysis of culture extracts from the predatory bacterium Herpetosiphon aurantiacus led to the discovery of the new natural product auriculamide, the structure of which was elucidated by MS and NMR analyses. The absolute configuration was determined, after hydrolysis, by chromatographic comparison with synthetic standards. A gene cluster for the biosynthesis of auriculamide is proposed.